That long road to equality: Judging from a gender perspective - Durand de Cassis, Analía Inés (2022)
The purpose of this paper is to develop some ideas on the state of the situation of the application of the gender perspective theory in the resolution of cases in the courts of justice of the province of Corrientes, Argentina. For this purpose, it is essential to deploy the theoretical framework under which this analysis will be made, which includes the issue of equality, as well as the constitutional view in relation to structural inequalities of social groups, which will lead to notice economic inequalities in the forms of human organization. Then, we will interpret what is understood by feminism, to reach the topic of what is judging from a gender perspective. This article ends with the presentation of the Tamara case, a paradigmatic case of femicide, resolved by the Superior Tribunal de Justicia de Corrientes [Court of Appeals in and for Corrientes], the highest court of said Argentinian province.